THE CAREER OF ANTANAS KLEMENTAS IN TELŠIAI LAND COURT - Stankevič, Adam (Teisė, 2016)
The article analysed facts from the professional biography of Antanas Klementas in the period of his life in the town of Telšiai. In historiography A. Klementas is known as a writer who, as one of the first, began to write Lithuanian poems on secular topics, however to his contemporaries he was primarily known as a high-ranking court official. In 1792 Antanas Klementas moved to Telšiai hoping to take office in the new Telšiai court of landed-gentry. He had worked for ten years in Telšiai court of landed-gentry, and later in the land court. Klementas pursued his career and held various positions with the help of the Pliateriai family whose lifelong faction member he was. In the last decade of the 18th century Klementas actively participated in the life of the Telšiai town and district: he had signed up as a citizen, became a vogt of Telšiai, and in 1794 participated in the rebellion directed against the Russian army. Klementas also took part in all the Telšiai district dietines that were held in the period of 1792–1817. A. Klementas reached the top of his career in the period of 1802–1817 in 1802–1809 and 1811–1814 he was the judge of the Telšiai land court, he used to be elected to other positions as well – he was a frontiers judge (1811), a standard bearer of Telšiai, more than once replaced the Marshal of Telšiai. Klement’s positions in the court guaranteed him a steady income that allowed him to purchase a considerable Gotautiškių estate. His work in the court and dietines in elective positions left an imprint on A. Klementas’ works.